PERANCANGAN MODUL LATIH ELEKTRO PNEUMATIC BERBASIS PLC - Ria Gazali; Lukas Fedianto; Muhammad Ganda Arya Permana; Syaifuddin Susilo Utomo (Institut Teknologi dan Bisnis Swadharma, 2022)
Pneumatics at this time plays an important role in the development of automation technology, in addition to hydraulics and electronics. The peneumatic automation system generally consists of a power source element, an input signal element, a signal processing element, a signal control element and an output element (aquator). To support knowledge about pneumatics, it is necessary to have pneumatic practicum supporting tools to increase student knowledge, one of which is props or electro pneumatic system practicum. The purpose of making this tool is so that students are able to design electro pneumatic training module tools and can also provide examples of applications using pneumatic automation systems in the industrial world. In the process of making this tool, the main process stages are the design of the pneumatic circuit and the framework of the pneumatic tool box, preparation of the main pneumatic circuit materials, manufacture of the framework, and installation of pneumatic components. All these processes are carried out correctly and result in a well-functioning electro pneumatic training module